Sleep apnoea - Hensley, Michael (BMJ Publishing Group, 2009)
INTRODUCTION: Sleep apnoea is the popular term for obstructive sleep apnoea-hypopnoea syndrome (OSAHS). OSAHS is abnormal breathing during sleep that causes recurrent arousals, sleep fragmentation, excessive daytime sleepiness, and nocturnal hypoxaemia. Apnoea may be "central", in which there is cessation of inspiratory effort, or "obstructive", in which inspiratory efforts continue but are ineffective because of upper airway obstruction. OSAHS affects up to 4% of men and 2% of women in the USA, with obesity being a major determinant. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical questions: What are the effects of treatment for severe obstructive sleep apnoea-hypopnoea syndrome? What are the effects of treatment for non-severe obstructive sleep apnoea-hypopnoea syndrome? We searched: Medline, Embase, The Cochrane Library, and other important databases up to May 2008 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 43 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: nasal continuous positive airway pressure (CPAP); measures aimed at improving compliance with CPAP; oral appliances; and weight loss.